Study on the kinetics of cation exchange resins as catalysts in free fatty acid (FFA) esterification of simulated used cooking oil - Nursofia, Mohd Yunus (2018)
Used cooking oil (UCO) is one of the potential substitutes for conventional biodiesel feedstock due to its low cost. In spite of its advantage, UCO has high free fatty acid (FFA) level which contributes to saponification reaction when it was directly utilised in base catalysed transesterification reaction. Ion exchange resins have been widely used in FFA esterification reaction to reduce the FFA content as this type of catalyst exhibits good catalyst performance in a short period of time. Nevertheless, conventional ion exchange resin has low acidic sites, moderate specific surface area and pore volume, poor durability and thermal stability. Therefore, in this study styrene-divinylbenzene (DVB) resins; RCP160M, RCP145H, PK228LH, PK216LH, PK208LH, SK104H and SK1BH with different textural and morphological properties were used as catalysts for the esterification of FFA in simulated used cooking oil (SUCO). These resins were characterised using Fourier transform-infrared spectroscopy (FT-IR), nitrogen physisorption, scanning electron microscopy (SEM), elemental analyser (CHNS), titration and particle size distribution (PSD) analyser to determine their physicochemical properties. These catalysts were screened to determine the best performance catalyst under reaction conditions of 300 rpm stirring speed, 5 wt. % catalyst loading, 60 ˚C and 12:1 methanol to oil mass ratio. The best performance catalyst was used in the subsequent studies focusing on the effect of mass transfer resistance, the effect of catalyst loading, reaction temperature, and methanol to oil mass ratio to investigate the best conditions in a batch mode system. The study proceeded with the kinetics of FFA esterification by developing three kinetic models; Pseudo homogeneous (P-H), Langmuir-Hinshelwood-Hougen-Watson (LHHW) and Eley-Rideal (Case I and Case II) to determine rate constant and activation energy of the reaction using POLYMATH 6.10 program. The results revealed that RCP160M was found to give the best catalytic performance as it outperformed the other catalysts and achieved maximum FFA conversions. This may attributed to the high specific surface area and total pore volume of RCP160M. 95 % of FFA conversion was achieved at the best reaction conditions with a stirring speed of 300 rpm, catalyst loading of 4 wt. %, a reaction temperature of 60 ˚C, and methanol to oil mass ratio of 18:1. During the reusability study, the catalytic activity of RCP160M decreased about 5-15 % for each cycle. The decrease of FFA conversion was due to pore blockage by oil during the reaction and simultaneously blocked the reactants from accessing the active sites. Besides, the loss of active sites during washing process might possibly occur between the reuse cycles. The kinetic results revealed that the experimental data were best-fitted to the E-R model (Case II) with the activation energy of 37.2 kJ/mol. This study showed that the reaction was limited by surface reaction where the adsorption of non-polar FFA molecules was more favourable than the adsorption of polar methanol molecules. In future, it was recommended that further work is necessary to improve the regeneration procedure of RCP160M as this catalyst can be potentially used as a catalyst for biodiesel production.